An Investigation of the Glucose Monitoring Practices of Nurses in Stroke Care: A Descriptive Cohort Study. (25th August 2013) - Laird, Elizabeth Ann; Coates, Vivien E.; Ryan, Assumpta A.; McCarron, Mark O.; Lyttle, Diane; Chaney, David
Abstract : Glucose derangement is commonly observed among adults admitted to hospital with acute stroke. This paper presents the findings from a descriptive cohort study that investigated the glucose monitoring practices of nurses caring for adults admitted to hospital with stroke or transient ischaemic attack. We found that a history of diabetes mellitus was strongly associated with initiation of glucose monitoring and higher frequency of that monitoring. Glucose monitoring was continued for a significantly longer duration of days for adults with a history of diabetes mellitus, when compared to the remainder of the cohort. As glucose monitoring was not routine practice for adults with no history of diabetes mellitus, the detection and treatment of hyperglycaemia and hypoglycaemia events could be delayed. There was a significant positive association between the admission hospital that is most likely to offer stroke unit care and the opportunity for glucose monitoring. We concluded that adults with acute stroke, irrespective of their diabetes mellitus status prior to admission to hospital, are vulnerable to both hyperglycaemic and hypoglycaemic events. This study suggests that the full potential of nurses in the monitoring of glucose among hospitalised adults with stroke has yet to be realised.